STRATEGI PEMASARAN SEBELUM DAN SETELAH PANDEMI COVID-19 (STUDI KASUS DI PRODUSEN WINGKO BABAT PADANGSARI) - Slahanti, Masine; Sulistyorini, Sulistyorini; Hidayah, Nining (Solusi, 2022)
Wingko Babat is a kind of cake made from young coconut, glutinous rice flour and sugar. Wingko is very famous on the north coast of the island of Java. This cake is often sold at train stations, bus stations or also in cake shops for family gifts. Wingko is usually round and usually served warm and cut into small pieces. Wingko can be sold in the form of large rounds or also in the form of small cakes wrapped in paper. The combination of sugar and coconut makes this cake delicious. Wingko has an important role for the economic growth of this region. Currently wingko is a popular food in Babat and Semarang with different brands and sizes being sold. Marketing strategy is one way to increase sales volume through a series of continuous ways. The research was conducted by the manufacturer of wingko tripe Padangsari Banyumanik, Semarang. Methods of data collection is done by interview and observation. The results of the research show that the marketing strategy carried out by the Padangsari wingko babat producer is to sell to other sellers through resellers and reduce the selling price to the reseller, and change the wingko babat icon from a train to a night bus which has the characteristics of other wingko icons.. Through the 4P marketing strategy, namely price, product, promotion, and place. Through the 4P marketing strategy, it is hoped that sales from Wingko Babat will increase more than before the Covid-19 pandemic.